The Utilization Of Coconut Tree Stumps Into Chairs - Saputra, Devi Satria; Riska, Urma; Amri, Asbahrul; Ben, Hasbaini (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
The coconut trees were one of the commodity crops in South Aceh which were multifunctional trees because almost all parts of the coconut tree can be used. One part of the coconut tree that can be used was the coconut tree stump which can be processed into chairs. The aim of this research was to design chairs from coconut tree stumps, made chairs from coconut tree stumps and determine the ergonomic value of coconut tree stump chairs. The result of this research was the creation of a new innovative chair made from coconut tree stumps which has an overall height of 79 cm, chair back height 32.5 cm, chair back width 64 cm, seat depth 46 cm, armrest height 16 cm, and leg height 34 cm. Coconut tree stump chairs were made through several processes, namely the process of taking raw materials, the process of making chair patterns, the scraping process, the sanding and varnishing process. The coconut tree stump chair was a chair that was not ergonomic, because there were several parts of the coconut tree stump chair that did not comply with the concept of ergonomics.